Dietary docosahexaenoic acid supplementation enhances expression of fatty acid‐binding protein 5 at the blood–brain barrier and brain docosahexaenoic acid levels. Issue 2 (30th July 2018) - Pan, Yijun; Morris, Elonie R.; Scanlon, Martin J.; Marriott, Philip J.; Porter, Christopher J. H.; Nicolazzo, Joseph A.
Abstract: The cytoplasmic trafficking of docosahexaenoic acid (DHA), a cognitively beneficial fatty acid, across the blood–brain barrier (BBB) is governed by fatty acid‐binding protein 5 (FABP5). Lower levels of brain DHA have been observed in Alzheimer's disease (AD), which is associated with diminished BBB expression of FABP5. Therefore, up‐regulating FABP5 expression at the BBB may be a novel approach for enhancing BBB transport of DHA in AD. DHA supplementation has been shown to be beneficial in various mouse models of AD, and therefore, the aim of this study was to determine whether DHA has the potential to up‐regulate the BBB expression of FABP5, thereby enhancing its own uptake into the brain. Treating human brain microvascular brain endothelial (hCMEC/D3) cells with the maximum tolerable concentration of DHA (12.5 μM) for 72 h resulted in a 1.4‐fold increase in FABP5 protein expression. Associated with this was increased expression of fatty acid transport proteins 1 and 4. To study the impact of dietary DHA supplementation, 6‐ to 8‐week‐old C57BL/6 mice were fed with a control diet or a DHA‐enriched diet for 21 days. Brain microvascular FABP5 protein expression was up‐regulated 1.7‐fold in mice fed the DHA‐enriched diet, and this was associated with increased brain DHA levels (1.3‐fold). Despite an increase in brain DHA levels, reduced BBB transport of 14 C‐DHA was observed over a 1 min perfusion, possibly as a result of competitive binding to FABP5 between dietary DHA and 14 C‐DHA. This study has demonstrated that DHA can increase BBB expression of FABP5, as well as fatty acid transporters, overall increasing brain DHA levels. Abstract : Fatty acid‐binding protein 5 (FABP5) is involved in the blood–brain barrier (BBB) transport of docosahexaenoic acid (DHA), an omega‐3 fatty acid required for normal brain function. Reduced brain DHA and BBB expression of FABP5 has been observed in a mouse model of Alzheimer's disease. As fatty acids can up‐regulate the expression of FABP isoforms in other tissues, the aim of this study was to determine whether DHA can up‐regulate the BBB expression of FABP5, thereby enhancing its own uptake into the brain. This study demonstrated that FABP5 at the BBB can be up‐regulated by DHA, which is associated with increased brain DHA levels.